Review of the status of the genus Phelene stat. resurr. (Orthoptera: Tetrigidae: Lophotettiginae) and description of a new species - Cadena-Castañeda, Oscar J.; Díaz, Carlos Julio Arango; Silva, Daniela Santos Martins; Buitrago, Oscar; García, Alexander García; Tumbrinck, Josef (Zootaxa, 2021)
The status of the genus Phelene stat. resurr., previously synonymized under Chiriquia is revalidated. The genus is redescribed and Phelene turgida stat. rev. a lectotype and paralectotypes are designated for this species. Tetrix laticeps is proposed as nomen dubium and its described a new additional species Phelene maroon n. sp. The diagnosis of the subfamily is adjusted with the characters of the new taxa included and an updated key of genera and species is provided.